STUDY OF THE HISTOLOGICAL AND BIOCHEMICAL EFFECT OF INSTANT NOODLES ON THE KIDNEY AND LIVER ON RATS MODEL (FUDMA JOURNAL OF SCIENCES, 2024)
Instant noodle is produced from flour, and sold in dried form in packets. The noodles are easy and quick in preparation to eat, it can also eat as snacks or as main food. The aim of this research is to investigate the effects of noodle with and without seasoning on the histology as well as biochemical parameters of liver and kidney on rats’ model. Three groups of 5 Wistar rats were used, they were fed with noodle with and without seasoning for the period of 28 days. After 28 days the blood of rats was collected for biochemical analysis, the rats were also sacrificed, liver and kidney were removed for histological analysis. Histological results show only a little change in the architecture of the liver and kidney, but only small amount of fat droplet in liver section. The Liver and Kidney tests didn’t show any changes in their parameters, only little increase in urea level of the kidney. Conclusively from this research, it was revealed no much effect of consuming instant noodle in rat model.
Keywords: Noodle; Wistar rat; Seasoning; Liver; Kidney